ACO2 homozygous missense mutation associated with complicated hereditary spastic paraplegia. (April 2018) - Bouwkamp, Christian G.; Afawi, Zaid; Fattal-Valevski, Aviva; Krabbendam, Inge E.; Rivetti, Stefano; Masalha, Rafik; Quadri, Marialuisa; Breedveld, Guido J.; Mandel, Hanna; Tailakh, Muhammad Abu; Beverloo, H. Berna; Stevanin, Giovanni; et al.
Abstract : Objective: To identify the clinical characteristics and genetic etiology of a family affected with hereditary spastic paraplegia (HSP). Methods: Clinical, genetic, and functional analyses involving genome-wide linkage coupled to whole-exome sequencing in a consanguineous family with complicated HSP. Results: A homozygous missense mutation was identified in the ACO2 gene (c.1240T>G p.Phe414Val) that segregated with HSP complicated by intellectual disability and microcephaly. Lymphoblastoid cell lines of homozygous carrier patients revealed significantly decreased activity of the mitochondrial aconitase enzyme and defective mitochondrial respiration. ACO2 encodes mitochondrial aconitase, an essential enzyme in the Krebs cycle. Recessive mutations in this gene have been previously associated with cerebellar ataxia. Conclusions: Our findings nominate ACO2 as a disease-causing gene for autosomal recessive complicated HSP and provide further support for the central role of mitochondrial defects in the pathogenesis of HSP.